Evaluation of Land Suitability for Teak (Tectona grandis L.) and Peanut (Arachis hypogaea L.) Agroforestry Development in the Upper Solo Sub-watershed - Wirawan, Bambang; Ifeanyi, Isife kenneth (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aims to determine the land suitability class for teak (Tectona grandis L.) and peanut (Arachis hypogaea L.) plants in the agroforestry area in the Solo Hulu Sub-DAS, and to assess the economic feasibility of the cultivation system in supporting sustainable land use. Methodology: The descriptive-exploratory survey method with stratified random sampling, field soil survey, pedon observation, analysis of physical and chemical properties of soil in the laboratory, GIS-based spatial analysis using ArcView 3.3, GPS tools, altimeters, clinometers, Munsell Soil Color Charts, pH meters, soil drills, land suitability matching methods, R/C ratio farming analysis, and in-depth interviews with farmers. Main Findings: Land suitability for teak plantations is generally classified as unsuitable (N), with limiting factors including dry season duration, soil depth, drainage, slope gradient, and erosion hazard. Peanuts are also predominantly unsuitable due to high rainfall and steep slopes. Nevertheless, both agroforestry systems remain economically viable, with a R/C ratio of 20.22 for teak and 2.02 for peanuts. Novelty/Originality of this study: This research integrates biophysical land suitability evaluation with economic feasibility analysis of a teak-peanut agroforestry system in the Upper Solo Sub-watershed. This study provides specific recommendations related to land-limiting factors and improvement strategies, thereby enriching scientific information for sustainable agroforestry planning in marginal sub-watershed areas.